2019
DOI: 10.1002/cite.201800076
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing a Cooling‐Condensing Tower

Abstract: Heat recovery from a flue gas stream by cooling and condensation in a packed bed column is widely used to increase plant's energy efficiency. Mass transfer equipment manufacturers have the possibility to optimize the size of such cooling towers and therefore its derived investment costs through selection of best suitable mass/heat transfer components. In this work, a real industrial design case of a cooling-condensing tower equipped with different high capacity random and structured packings is presented. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…With the development of water treatment technology, the advantages of hybrid condensers are becoming more and more evident as the cost of the condenser decreases, and the importance of its use is gradually gaining emphasis. Studies have shown that the presence of fillers can effectively improve the mass and heat transfer performance of distillation, 5 absorption, 6,7 and other unit operations.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of water treatment technology, the advantages of hybrid condensers are becoming more and more evident as the cost of the condenser decreases, and the importance of its use is gradually gaining emphasis. Studies have shown that the presence of fillers can effectively improve the mass and heat transfer performance of distillation, 5 absorption, 6,7 and other unit operations.…”
Section: Introductionmentioning
confidence: 99%